Epidermodysplasia verruciformis associated with sensorineural hearing loss in a 9 years old boy. - Karrabi, M.; Karrabi, N.; Karrabi, M. (European Journal of Pediatric Dermatology, 2019)
Epidermodysplasia verruciformis (EV) is an uncommon genetic disorder resulting in disseminated wart-like lesions as a consequence of immune dysfunction in response to non-pathogenic HPVs. Genetic studies have illustrated TMC family genes to contribute in both sensorineural hearing and immune defense against HPVs. Nevertheless, there is just another clinical report of this association. Here we present a 9 years old boy with EV and sensorineural hearing loss to highlight the genetic basis of this association.